A9.13 TNF-Induced- Protein Tyrosine Phosphatase Nonreceptor Type 2 (PTPN2) as a Negative Regulator of Inflammation in Rheumatoid Arthritis. (25th February 2013) - Aradi, Borbala; Filkova, Maria; Kasper, Stephanie; Klein, Kerstin; Scharl, Michael; Michel, Beat A; Gay, Renate E; Buzas, Edit I; Gay, Steffen; Jüngel, Astrid
Abstract : Background and Objectives: Protein Tyrosine Phosphatase Nonreceptor Type 2 (PTPN2) is a protein tyrosine phosphatase that plays a role in the development of autoimmune diseases. PTPN2 function has not been studied in rheumatoid arthritis (RA), although single nucleotide polymorphisms within the gene have been described to be associated with RA in genome wide association studies. Considering the involvement of PTPN2 in the regulation of key inflammatory pathways, our aim was to analyse the expression and function of PTPN2 in RA synovial fibroblasts (RASF). Materials and Methods: The expression of PTPN2 was assessed in synovial tissue and fibroblasts (passage 4–10) from patients with RA and osteoarthritis (OA) using immunohistochemistry, real-time PCR (w/o tumour necrosis factor α (TNFα), IL1β, LPS and hypoxia) and Western blotting. PTPN2 was silenced with silencing RNA. Levels of IL-6 and IL-8 expression were measured by commercially available ELISA in cell culture supernatants after silencing PTPN2 in RASF w/o stimulation with tumour necrosis factor α (TNFα). Apoptosis of RASF was evaluated by AnnexinV staining using flow cytometry after stimulation with TNF-related apoptosis-inducing ligand (TRAIL, 20 ng/ml) for 24 hours. Results: In RA synovial tissue, compared with OA, we observed a stronger staining of ptpn2 in both the lining and the sublining layer by immunohistochemistry. On mRNA level we confirmed this overexpression in RA synovial tissue (2.0 fold, n = 4–5). In isolated RASF the constitutive mRNA level of PTPN2 was higher than in OASF (1.6 fold, p < 0.01, n = 10–16). Levels of PTPN2 were further upregulated in RASF after stimulation with inflammatory cytokines such as TNFα (10 ng/ml, 24 hours, 3.1 fold, p < 0.05, n = 4), TNFα and IL-1β (1 ng/ml, 2.3 fold, n = 5), LPS (100 µg/ml, 24 hours, 1.9 fold, n = 5) and by 1% hypoxia (1.3 fold, n = 3). Accordingly, basal PTPN2 protein expression was 2.0 fold higher in RASF than in OASF (n = 4) and TNFα upregulated levels of PTPN2 (1.7 fold). ptpn2-deficient RASF produced 2.4 times more IL-6 than scrambled siRNA transfected cells (mean ± SD pg/ml 11412 ± 6313 versus 28133 ± 12734, n = 3). On the other hand, levels of IL-8 were not affected (35800 pg/ml versus 24330 pg/ml, n = 3). Furthermore, after silencing, 34% increase in TRAIL-induced apoptosis was detected in RASF (n = 5) compared to scrambled controls. Conclusions: Our findings indicate that PTPN2, known to be involved in the pathogenesis of several autoimmune diseases, could be an important negative regulator of inflammation in RASF. Acknowledgement: This work was supported by IMI BTCure, IAR and Masterswitch-FP7.